Appropriate Timing of Coronary Artery Bypass Grafting after Acute Myocardial Infarction - Assmann, Alexander; Boeken, Udo; Akhyari, Payam; Lichtenberg, Artur (The Thoracic and Cardiovascular Surgeon, 2012)
Objectives Optimal timing of coronary artery bypass grafting (CABG) after acute myocardial infarction (AMI) remains the subject of fierce debate. Therefore, the recommended deferral ranges from immediate intervention to surgery 4 weeks after infarction. Especially, the increasing cohorts of patients at old age or with poor left ventricular function, whose mortality rates are additionally enhanced, may profit from focused analyses. This study aims at clarifying the appropriate timing of CABG after AMI, with special regard to high-risk patients (Age >70 years, left ventricular ejection fraction (LVEF) <30%).Methods Retrospective analysis was performed in 3475 patients who had undergone isolated CABG between 2005 and 2009. Those 1168 patients with previous AMI (<30 days) were categorized in groups, depending on deferral of surgery: <6 hours after AMI (A), 6 hours–1 day (B), 2–3 days (C), 4–10 days (D), 11–20 days (E), and 21–30 days (F). Furthermore, subgroups with an age >70 years or a LVEF <30% were examined.Results The mortality rates in groups A–F were 14.8, 10.2, 8.8, 4.2, 2.3, and 2.0%, whereas only the values of groups A–D were significantly increased versus the mortality rate of patients without previous AMI (1.9%). In patients over 70 years, we observed operative mortalities of 26.3, 14.3, 11.9, 6.1, 4.2, and 3.1% (groups A–F) versus 2.5% (no previous AMI), while 27.4, 15.4, 11.7, 6.0, 3.7, and 2.8% (groups A–F) versus 2.7% (no previous AMI) of patients with a LVEF <30% died during the first 30 days after surgery. In both subanalyses of high-risk patients, the enhanced mortalities of groups A–E reached significance. Multivariate analysis of operative risk factors revealed that CABG within 10 days after AMI and age over 60 years are independently associated with operative mortality.Conclusions CABG early after AMI (<10 days) is accompanied by significantly increased mortality, especially in elderly patients or in patients with a severely impaired LVEF. At least the critical time period of 3 days should be avoided–whenever the hemodynamics is stable enough.
Keywords: acute myocardial infarction; coronary artery bypass grafting; surgical timing; operative mortality; delayed revascularization